2019
DOI: 10.1038/s41563-019-0323-6
|View full text |Cite
|
Sign up to set email alerts
|

An integrin αIIbβ3 intermediate affinity state mediates biomechanical platelet aggregation

Abstract: Integrins are membrane receptors mediating cell adhesion and mechanosensing. The structure-function relationship of integrins remains incompletely understood, despite the extensive studies due to its importance to basic cell biology and translational medicine. Using fluorescence dual biomembrane force probe, microfluidics and cone-and-plate rheometry, we applied precisely-controlled mechanical stimulations to platelets and identified an intermediate state of integrin α IIb β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(197 citation statements)
references
References 71 publications
(124 reference statements)
10
187
0
Order By: Relevance
“…We for the first time derive a threshold of ~1 nN per cell-substrate adhesion to activate αIIbβ3 integrins to form 3D fibrils ( Figure 4). The ECM proteins from the vessel wall and the thrombus thus essentially instruct the platelets to adopt distinct phenotypes of medium and high contractility, respectively, probably serving different functions as guided by different levels of mechanosensitive integrin signaling (Strohmeyer et al 2017;Chen et al 2019). This mechanism in platelets is, probably due to their small size and the high abundance of αIIbβ3 integrins, different from fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We for the first time derive a threshold of ~1 nN per cell-substrate adhesion to activate αIIbβ3 integrins to form 3D fibrils ( Figure 4). The ECM proteins from the vessel wall and the thrombus thus essentially instruct the platelets to adopt distinct phenotypes of medium and high contractility, respectively, probably serving different functions as guided by different levels of mechanosensitive integrin signaling (Strohmeyer et al 2017;Chen et al 2019). This mechanism in platelets is, probably due to their small size and the high abundance of αIIbβ3 integrins, different from fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…6 Single-cell biophysical techniques and their sensitivity have enabled quantification and unveiling of previously unknown relationships and fundamental paradigms in platelet biology and their underlying biomechanical principles with a resolution up to single-molecule level. [7][8][9][10] However, many of these single-cell techniques are still limited in their ability to scale to measure a suitably large number of individual cells and independent samples. 11 In this review, we focus on biophysical methods suitable to assess and quantify biomechanical characteristics such as elastic modulus, stiffness (or deformability), forces generated during adhesion, and spreading and contraction of single platelets in health and disease states.…”
Section: Why Should We Investigate Biomechanical Properties Of Singmentioning
confidence: 99%
“…Given the extent of cell‐to‐cell variations, rare subpopulations, and intrinsic fluctuations within biological systems, bulk population‐level experiments often conceal and average out vital causal relationships underlying the biological phenomena . Single‐cell biophysical techniques and their sensitivity have enabled quantification and unveiling of previously unknown relationships and fundamental paradigms in platelet biology and their underlying biomechanical principles with a resolution up to single‐molecule level . However, many of these single‐cell techniques are still limited in their ability to scale to measure a suitably large number of individual cells and independent samples .…”
Section: Introductionmentioning
confidence: 99%
“…24 Using a stenosed microfluidic model, we demonstrated that the biomechanical platelet aggregation is mainly supported by integrin αIIbβ3 with an extended-closed (EC) conformation (A). 25 We also developed a dual biomembrane force probe to visualize integrin biomechanical activation on a living platelet. 26 We found that, upon mechano-signaling of GPIb, αIIbβ3 adopts the EC conformation and possesses affinity and bond lifetime that are intermediate between the well-characterized active and resting states.…”
Section: Cellular Controls On Weibel-palade Bodies Affecting Von Willmentioning
confidence: 99%